Physical properties of metalloporphyrins - Skyte, P (1978)
In this work, a number of physical techniques are used to study the behaviour and properties of different metalloporphyrin systems under varying conditions. The behaviour of these systems is interpreted so far as is possible in terms of relations between structure, both geometrical and electronic, and function. In Chapter 1, a general survey of porphyrin structure, activity, properties and relevance is provided as an introduction. The significance of porphyrins in the biological context is briefly discussed, and arguments are presented to justify the scope of model systems in providing an understanding of larger biological systems. Chapter 2 is concerned with the basic theory and practice of the physical techniques employed. In Chapter 3, the electronic properties of iron porphyrin derivatives in which spin crossover phenomena are present are studied. With certain derivatives, unusual and anomalous features manifest themselves in the magnetic moment and PMR, Mössbauer and electronic absorption spectroscopic data. These results are discussed and interpreted in terms of a number of theories of increasing sophistication. In Chapter 4, PMR studies of some 'natural' ferric porphyrin complexes are described. Paramagnetic spectral shift data are obtained, analysed and interpreted in terms of a valid spin delocalisation theory. The effect of substituents on the porphyrin ring and on the axial ligand upon the bonding interactions is observed. In Chapter 5, some mixed ligand ferric octaethylporphin derivatives are studied by means of PMR spectroscopy. Hyperfine interaction data are obtained and partially rationalised in terms of spin density distribution at particular axial ligand positions. In Chapter 6, some monomer and oxo-bridged dimer porphodimethene ferric complexes are studied by means of PMR spectroscopy in order to examine the effect of partial saturation at the porphyrin periphery on bonding interactions, and on electron spin transfer from the iron atom.